New Insights Into Functions and Possible Applications of Clostridium difficile CRISPR-Cas System - Maikova, Anna; Severinov, Konstantin; Soutourina, Olga (Frontiers in Microbiology, 2018)
Over the last decades the enteric bacterium Clostridium difficile (novel name Clostridioides difficile) - has emerged as an important human nosocomial pathogen. It is a leading cause of hospital-acquired diarrhea and represents a major challenge for healthcare providers. Many aspects of C. difficile pathogenesis and its evolution remain poorly understood. Efficient defense systems against phages and other genetic elements could have contributed to the success of this enteropathogen in the phage-rich gut communities. Recent studies demonstrated the presence of an active CRISPR (clustered regularly interspaced short palindromic repeats)-Cas (CRISPR-associated) subtype I-B system in C. difficile. In this mini-review, we will discuss the recent advances in characterization of original features of the C. difficile CRISPR-Cas system in laboratory and clinical strains, as well as interesting perspectives for our understanding of this defense system function and regulation in this important enteropathogen. This knowledge will pave the way for the development of promising biotechnological and therapeutic tools in the future. Possible applications for the C. difficile strain monitoring and genotyping, as well as for CRISPR-based genome editing and antimicrobials are also discussed.